Contribution à l’étude de l’influence du jeun de ramadan chez les hommes diabétiques de type 2 sous thérapie aux biguanides - Bouhadja, Fatma (My University, 2021)
Diabetes mellitus is a métabolic disease characterized dy chronic hyperglycemia resulting from defective insulin secretion or insulin action or from both associated for a long time with specific organic complication , particularly affecting the eyes , kidneys ,nerves , heart and blood vessels. Ramadan represents the sacred month of the year when muslims are supposed to refrain from eating ; drinkin and having sex from sunrise to sunset. This month provides an excellent research model for studing changes in eating habits and their consequences on changes on weight status as well as fasting metabolism in people with type 2 diabetes.eleven (11) diabetic men , aged over 40 years , on oral anti-diabetic with biguanide were included in the study. Measurements and controls were carried out in the patients on the 15th days the Ramadan and the 15th day after ramadan and concerned : glycemia ; triglycerides ; cholesterol ; Creatinine and urea . The results underwent a single- factor block-factor variance analysis and a comparison of two-point means according to the Newman and Keuls test. The fasting of ramadan does not seem to affect in men with type 2diabtes under biguanide therapy the glycemic balance and the plasma lipid balance, particularly the level of plasma triglycerides, which seems to be markedly improved .in addition, i twas found during the period of fasting food restriction that the patients showed no hypoglycemia or hyperglycemia and no renal dysfonction that could prevent them from fasting .
Keywords: type 2 diabetes, ramadan youth, biochemical parameters, bigunide.